Magnetic fluid hyperthermia: Advances, challenges, and opportunity. (9th October 2013) - Kozissnik, Bettina; Bohorquez, Ana C.; Dobson, Jon; Rinaldi, Carlos
Abstract: Though the concepts of magnetic fluid hyperthermia (MFH) were originally proposed over 50 years ago, the technique has yet to be successfully translated into routine clinical application. Significant challenges must be addressed if the field is to progress and realise its potential as an option for treatment of diseases such as cancer. These challenges include determining the optimum fields and frequencies that maximise the effectiveness of MFH without significant detrimental off-target effects on healthy tissue, achieving sufficient concentrations of magnetic nanoparticles (MNPs) within the target tumour, and developing a better mechanistic understanding of MNP-mediated energy deposition and its effects on cells and tissue. On the other hand, emerging experimental evidence indicates that local thermal effects indeed occur in the vicinity of energy-dissipating MNPs. These findings point to the opportunity of engineering MNPs for the selective destruction of cells and/or intracellular structures without the need for a macroscopic tissue temperature rise, in what we here call magnetically mediated energy delivery (MagMED).